Caracterização da liga Ti-15Zr visando aplicações biomédicas - Silva, Jean Michel da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
With advances in health care, has been na increase of demand for material that could replace the functions of the human body parts, thus evolved biomedic prosthesis which today are responsible for the constant improvement of the quality of life. The Titanium alloys are widely used as implants due to its properties, like high mechanical resistance, biocompatibility and corrosion resistance, and the addition alloying elements like Zirconium, may improve some of those properties. Such properties are related to the microstructure and consequently to the type of processing performed. The purpose of this dissertation was to characterize the experimental alloy Ti15Zr after route of processsing and heat treatment in order to extend the knowledge about this alloy. The latter has been abtained by fusion of pure metals in a arc melting furnace with an inert argon atmosphere. The material has been homogenized in a tube furnace at 950ºC for 24h and cold worked by swaging, after that, bars with 10 mm of diameter were obtained by the process of rotary forging. The samples were solubilized at 900º C for 2 hours and quenched in water. After that, 4 samples were submitted to the aging, at 400º C, 450º C, 500º C and 550º C. The microstructure and phase analysis was done by optical microscopy and X-rays diffraction (XRD), the mechanical characterization was carried out by microhardness test and finally, evaluation of corrosion resistance of the alloy by electrochemical tests. The XRD and the optical microscopy made it possible to analyze that the heat treatment influenced the phase shifting from α to α', and probably affected the alloy hardness, at the first aged sample at 500º Chas been a sudden increase in the value of hardness, probably by appearance of omega phase, unwanted phase to the medical application duo to great fragility, and finally ... (Complete abstract click electronic access below)

Com os avanços na área de saúde aumentou-se a demanda por materiais que substituíssem as mesmas funções de partes do corpo humano, assim foram evoluindo as próteses biomédicas que hoje são responsáveis pela melhora constante na qualidade de vida. As ligas de titânio são muito utilizadas como implantes devido às propriedades como alta resistência mecânica, biocompatibilidade e resistência à corrosão, e a adição de elementos de liga como o zircônio, pode melhorar algumas dessas propriedades. Tais propriedades estão relacionadas à microestrutura e consequentemente ao tipo de processamento realizado. O objetivo deste trabalho foi caracterizar a liga experimental Ti15Zr após uma rota de processamentos e tratamentos térmicos para maior conhecimento da liga. Esta foi obtida pela fusão dos metais puros em um forno a arco voltaico com atmosfera inerte de argônio. O material foi homogeneizado em um forno tubular a 950 °C por 24 h e deformadas a frio pelo processo de forjamento rotativo para obtenção de barras com 10 mm de diâmetro. As amostras foram solubilizadas a 900°C por 2 horas e temperadas em água. Após foram cortadas 4 amostras, que foram submetidas ao envelhecimento, a 400°C, 450°C, 500°C e 550°C. A análise microestrutural e de fase foi feita através da microscopia óptica e difração de raios X (DRX), a caracterização mecânica foi realizada pelo ensaio de microdureza e por fim, a avaliação da resistência à corrosão da liga por ensaios eletroquímicos. A partir do DRX e da microscopia óptica foi possível analisar que os tratamentos térmicos influenciaram na transformação de fase α para fase α, essa mudança afetou a dureza da liga, na primeira amostra envelhecida, a dureza caiu pois acredita-se que houve um rearranjo e crescimento dos grãos que favoreceu esse fato. Na segunda ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ligas de titanio; Materiais resistentes a corrosão; Materiais biomédicos; Microestrutura; Titanium alloys